A novel bio-inspired anti-vibration structure for operating hand-held jackhammers. (1st March 2019) - Jing, Xingjian; Zhang, Linli; Feng, Xiao; Sun, Bo; Li, Quankun
Highlights: A bio-inspired anti-vibration structure is employed, for the first time, for vibration suppression of hand-held jackhammers. The nonlinear stiffness of the structure demonstrates very beneficial high-static-low-dynamic property. The nonlinearity can offer a decreasing stiffness subject to increasing compression of the structure, a unique nonlinear property. Most detrimental vibration to hands and arms can be obviously suppressed. The resulting technology is very simple and successfully solves this vibration problem in construction for many years. Abstract: Long-term exposure to high level vibration can lead to considerable pain and time off work, and even result in permanent disability. Therefore, vibration protection to operator when operating vibrating tools is a very important issue in construction. Targeted at operating heavy-duty jackhammers or road breakers etc, an innovative anti-vibration exoskeleton technology is successfully developed in this study, which is passive, portable, cost-efficient and crucially helpful for a significant vibration suppression during the drilling and hitting process. To explore the benefits of nonlinear dynamics and passive structure design in vibration control, the innovative anti-vibration exoskeleton is designed for the first time to mimic the limb structure of animals and fully employs the beneficial nonlinear benefits in the bio-inspired anti-vibration structure which can consequently significantly reduce vibration transmission without sacrificing loading capacity, while the latter is very important to increase the demolition efficiency during a demolishing work. Theoretical modeling, simulation and experiment results demonstrate the effectiveness and efficiency of this innovative technology, consequently solving such a long-time existing engineering problem in the construction field.